Human-AI Collaboration in Management: Its Impact on Efficiency and Performance - Berilian Ayu Kusuma (PT. Anagata Sembagi Education, 2026)
ABSTRACT Human–AI collaboration has emerged as a transformative approach in modern management, combining the computational power of artificial intelligence with human intuition, creativity, and ethical judgment. This study aims to analyze the impact of human–AI collaboration on organizational efficiency and performance, with a focus on collaboration design, trust, and organizational context. The research adopts a qualitative approach using a systematic literature review and document analysis of recent peer-reviewed studies. Data are analyzed through thematic and qualitative content analysis to identify key patterns related to efficiency, decision quality, and performance outcomes. The findings reveal that human–AI collaboration enhances efficiency through task automation, predictive analytics, and reduced cognitive load, while also improving decision-making accuracy and consistency. However, the effectiveness of this collaboration depends on role complementarity, trust in AI, employee capability, and supportive organizational culture. The discussion highlights that balanced integration between human and AI capabilities is essential to achieve sustainable performance improvements. In conclusion, human–AI collaboration serves as a strategic enabler of organizational performance when supported by appropriate design, governance, and human resource development.